(3TQM GdaUjMs - (3CHh GdbGSe YHO Gddg Hf eMeO Hf GdMSjf Hf fGbjG Hf OGhO (B( (3GdHfOGQ(B)s; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3gPG cJGH CeddfGg ai TQM cJGH GdaUjM hEVGMg , hGdJfHjg Ydi eG CZdadg hGVYg hGSJOQGcg , hPcQ eG YKQ Ydjg ajg , heG GMJL dg Hg s
(3BNQgG (B:s
(3jbGd adGf eSNO ef GdMei Ci eKbd hbGd Ph GdQeI ai CLhfI GdhQO hJZjQg UQi BSjf jRhi dg GdeQA hLgI hdhPGbg GdXeBf ai TgQ fGLQ GfJgi TQM cJGH GdaUjM Ydi eG TQWfGg ef EjVGM SHdg hYOdfG Yf GdJJHY dg hGdMeOddg s
(3GdaUjM ai GddZI GfXQ cTa GdXfhf L(B2 (3U` (B1272s
(3HChdgG hba SfI (B1239 (3g`s
(3hHgG fXGe GdJYbjHIs
(3HBNQgG fMh (B12 (3hQbI ajgG fbhd eNJdaI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GddZIs